Evaluation of thyroid cytology using the Bethesda system for reporting thyroid cytopathology: An institutional experience - Basnet, Dipika; Makaju, Ramesh; Gautam, Nikita; Shrestha, Binaya; jha, Sumit; Budhathoki, Arjun (Journal of Chitwan Medical College, 2025)
Introduction: Fine-needle aspiration cytology (FNAC) is a rapid, cost-effective and safe to evaluate thyroid nodules. The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) offers a standardized reporting system for FNAC. This study aimed to categories thyroid FNAC according to TBSRTC and evaluate its accuracy with histopathology examination (HPE) report. Method: This was a cross-sectional study of retrospectively collected data of thyroid FNAC and HPE during Jul 2022 to Aug 2024 in the Department of Pathology at Dhulikhel Hospital, Kathmandu University Hospital, Nepal. All FNAC specimens of thyroid received were included, categorized as per TBSRTC and compared with the available HPE report for accuracy (true positive + true negative/total number of cases). The study was approved by the institutional review board. Data analysis was performed using IBM SPSS. Result: Out of 152 thyroid FNAC non-diagnostic were 14(9.2%), benign 86(56.6%), atypia of undetermined significance (AUS) 7(4.6%), follicular 4(2.6%), suspicious for malignancy 13(8.6%), and malignant were 28(18.4%). Sensitivity was 100% and specificity 90.9%. The positive predictive value and negative predictive value were 93.3%% and 100% respectively. The accuracy of FNAC in differentiating benign from malignant was 96%. The malignancy rate for benign, atypia of undetermined significance, follicular neoplasm, suspicious for malignancy, and malignant categories were 0%, 33.3%, 33.3%, 75%, and 93.3%, respectively. Conclusion: Our study affirms accuracy of TBSRTC with gold standard histopathology. However, the malignancy rate of AUS was higher than the risk mentioned in TBSRTC, and warrants further workup including ultrasound or thyroid scan in addition to repeat FNAC